COST-EFFECTIVENESS ANALYSIS OF INSULIN REGIMEN ON TYPE 2 DIABETES MELLITUS OUTPATIENT IN DENPASAR MUNICIPALITY - Larasanty, Luh Putu Febryana; Sarasmita, Made Ary; Putra, I Gusti Ngurah Agung Dewantara (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Insulin is one of the antidiabetic agents that available for the treatment of type 2 diabetes mellitus (T2DM) patients. Insulin has several types of formulation, with its cost and effectiveness. The aim of this study was to compare the cost-effectiveness of insulin regimen in the therapy management of T2DM outpatient. Methods: Cost-effectiveness analysis has been done by calculating the average cost-effectiveness ratio (ACER) and incremental cost-effectiveness ratio (ICER) of each insulin regimens. Effectiveness was measured by improvement of fasting blood glucose, postprandial blood glucose, and HbA1c value. The total cost of insulin regimen was calculated from direct medical cost, direct nonmedical cost, and indirect nonmedical cost. Results: Overall, 42 patients meet the inclusion criteria were included this study. There were four insulin regimens compared, namely, insulin detemir,premixed insulin aspart, insulin aspart, and a combination of insulin aspart + insulin glargine. The combination of insulin aspart + insulin glargine provides pre-eminent therapy effectiveness (58.82%), whereas insulin detemir regimen has the lowest total cost (102.62 USD). Calculation of ACER showed that insulin aspart has the lowest ACER value, in an amount of 1.91 USD per percentage of effectiveness. Based on ICER value, insulin aspart was the better choice compared to the combination of insulin aspart + insulin glargine (0.18 USD vs. 0.82 USD). Conclusion: The variation of therapeutic effectiveness and total cost was observed in the management of T2DM outpatient. Based on ACER and ICER value, insulin aspart was the most cost-effective insulin compared to another insulin regimen on the study.